Ontogeny of biological nitrogen fixation in Phaseolus vulgaris - Hungria, Mariangela; Neves, Maria Cristina P. (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was performed, under greenhouse conditions, with two cultivars of Phaseolus vulgaris L. (Negro Argel and Venezuela-350) inoculated with either file strain CO5 or 127 K-17 of Rhizobium leguminosarum biovar phaseoli. Plants having the greatest nitrogen accumulation showed: the highest rates of nitrogenase activity between flowering and mid-pod filling stage; lower loss of ATP via the evolution of hydrogen in the nodules; higher rates of nitrogen transport in the xylem sap; higher percentage of nitrogen as ureides in the xylem sap; and higher nitrogen remobilization from the leaves and stems to the seeds. There was an effect of the bean cultivar, of the Rhizobium strain and of the interaction between cultivars and strains in all the parameters mentioned. The symbiosis of Negro Argel with CO5 accumulated 88% more nitrogen in seeds, lost less nitrogen in senescent leaves (N in senescent leaves/N in plants) and had a nitrogen harvest index (N in seeds/N in plants) 20% greater than the cultivar Venezuela-350 inoculated with strain 127 K-17.